J.J.Rousseau’nun “Sosyal Sözleşme” Eserinin Osmanlı Türkçesine İlk Tercümeleri II - AKKAYA, RÜKİYE (My University, 2020)
Tanzimat’tan Türkiye Cumhuriyeti’nin kuruluşuna değin, Fransız aydınlanmasını ve özellikle J.J.Rousseau’nun çalışmalarını okumak, Osmanlı Türkçesine çevirmek nesilden nesle geçmiştir. Sosyal Sözleşme’nin ilk tercümeleri üzerine bir fikir verebilecek olan elimizdeki örnekler; 1911’de İçtihȃd dergisinde yayınlanan birkaç sayfalık metin, 1904’te Paris’te yayınlanan eksik kalmış I.Kitap tercümesi ve nihayet 1911’de İstanbul’da yayınlanan tercümedir. Türkiyat Mecmuasında (C 27, Sayı 2) bu tercümeler üzerine bir analiz yayınlamıştım. Bu çalışmada, J.J.Rousseau’nun Sosyal Sözleşme kitabının, 1329 tarihli “Mukavele-i İçtimȃiyye yȃhûd Hukuk-ı Siyȃsiyye-i Kavȃidi Esȃsiyye” başlığı ile Osmanlı Türkçesine ilk tam metin çevirisi üzerinde; karşılaştırmalı olarak kaynak metin ve çeviri metin üzerinde bazı kavramların analizi yapılmıştır.

From the Tanzimat era until the establishment of Turkish Republic, reading the works of French_x000D_ Enlightenment philosophers, especially those of Jean-Jacques Rousseau, and translating them had been a_x000D_ practice that passed down one generation to the other. However, before the Tanzimat era, there had been_x000D_ also some studies which referred to the works of Rousseau, who was called as an atheist and paved the way_x000D_ for the French Revolution, 1789. The extant samples which can give us some ideas on the first translation_x000D_ of the Social Contract, are a few pages of an article published in a journal named “Ictihad” in 1911, an_x000D_ unfinished translation of “Book I” published in Paris in 1904 and other translations published in Istanbul_x000D_ in 1911. We distinguish the clear disproportion between the translation of Rousseau’s political works and_x000D_ the admiration for him among Ottoman intelligentsia, considering the translations of his works during the_x000D_ period from the Young Ottomans to the Young Turks._x000D_ I published an analysis on translations in Turkish Journal of History (C 27, Number 2). In this study,_x000D_ a comparative analysis of the first full text translation of the Social Contract book by J.J.Rousseau into_x000D_ Ottoman Turkish dated 1329 was made on the source text and the translation text._x000D_
The First Translations of J. J. Rousseau’s “Social Contract” into Ottoman Turkish II